"Get Thee to a Nunnery!": Uses of English Canadian Convent Archives Across Feminist Disciplines - Bondy, Renée (Atlantis, 2009)
The archives of Canadian convents house significant and plentiful resources. Until recent decades, these have been underutilized, particularly in English Canada. This paper examines the ways in which convent archives might be used by feminist researchers across the disciplines.